A qualidade de vida no trabalho sob a percepção dos servidores da Universidade Federal do Pampa - Lemos, Ricardo Brião (2015)
Public institutions, aiming to provide best quality services and to the welfare of civil servants, are implementing a personnel management restructuring, aimed at the promotion of Life Quality at Work (LQW). However, many institutions still only circumvent the problems faced in labor relations. Possibly the most appropriate would be following a trend set off for an assessment of the needs of their work teams, thus contributing in terms of grants for the preparation and development of a LQW Program, which would bring more comprehensive and lasting results. Also, the present study aims to analyze which LQW factors perceived as relevant by the employees of UNIPAMPA. Achieving this goal can serve as a basis for possible contribution to the development of LQWP the Rectory of Personnel Management (PROGESP). For this, the methodological procedure adopted seeks refuge in a descriptive, through a quali-quantitative approach, involving the use of questionnaires, interviews and document analysis about LQW servers, teachers and technical-administrative education system (TAE) of UNIPAMPA, beyond the search information about it by e-mail and/ or websites of other 4 Federal Universities of Rio Grande do Sul. The document analysis and data show IFES other actions focused on a LQW in an assistencialist and non preventive way, while they could start by collecting information, together with the servers, about the problems related to LQW. The results of qualitative analysis, ie, the interviews with the nine TAE PROGESP servers that are involved with the development of LQWP in the University, show that all attendees believe that the implementation of LQWP will enrich for both the individual and the institution as a whole. Finally, the results of questionnaires given to teachers and TAE regarding the perception of the LQW with the institution show that the factors related to the physical space and work tools, professional development opportunities, job satisfaction and relationship with peers positively influence satisfaction with LQW in UNIPAMPA.